The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/jmse9111260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flanks on Resistance Performance of High-Speed Amphibious Vehicle

Abstract: In order to reduce the additional resistance of high-speed amphibious vehicles, Flanks are designed on the concave grooves. As a new drag reduction attachment, the principle of Flanks is analyzed and discussed in detail. In this paper, the HSAV model and Flanks coupling resistance tests are performed based on the Reynolds-averaged Navier–Stokes method and SST k−ω model. The accuracy of the numerical approach is verified by a series of towing tests. Results show that with a fixed installation angle and invariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Yamashita et al [3] aimed to propose a methodology for simulating amphibious vessels transitioning between land and water modes. Sun et al [4] and Pan et al [5] conducted studies using experiments and simulations to improve resistance performance by adding flaps as attachments to reduce lateral resistance of high-speed amphibious vehicles. Liu et al [6] performed optimal design using CFD by selecting and analyzing shape control parameters as optimal design variables to reduce the hydrodynamic resistance of an amphibious vehicle, comparing the results with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Yamashita et al [3] aimed to propose a methodology for simulating amphibious vessels transitioning between land and water modes. Sun et al [4] and Pan et al [5] conducted studies using experiments and simulations to improve resistance performance by adding flaps as attachments to reduce lateral resistance of high-speed amphibious vehicles. Liu et al [6] performed optimal design using CFD by selecting and analyzing shape control parameters as optimal design variables to reduce the hydrodynamic resistance of an amphibious vehicle, comparing the results with experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, it has been demonstrated that installing stern flaps and underwater tail hydrofoils on amphibious vehicles can significantly enhance wave compression and resistance reduction [8][9][10][11][12]. Both these additions are instrumental in adjusting the vehicle's attitude and optimizing the flow field around the vehicle's hull [13].…”
Section: Introductionmentioning
confidence: 99%